Towards AI-Driven Mandarin Learning: Unlocking the Potential of Material Description Table for Indonesian Learners - Adhimas, Yogi Bagus; Amri, Miftachul; Deng, Boer (Proceeding of International Joint Conference on UNESA, 2025)
The study of applied contrastive analysis between Mandarin and Bahasa Indonesia has garnered increasing attention from researchers, particularly in language education and linguistic studies. This research aims to analyze key contrasting linguistic components between the two languages, specifically: number auxiliary words (量词 liàngcí), the occurrences of 了 (le), numbering rules, reduplication (重叠 chóngdié), and 离合词 (líhécí), a unique linguistic structure that has no equivalent in Bahasa Indonesia.This study employs a qualitative research approach with a narrative elaboration model. The primary data source consists of officially recommended textbooks by the Confucius Institute (孔子学院总部): 标准教程 Standard Course HSK 1–6下. The data analysis techniques include identification, classification, and structured presentation of findings. The results reveal a significant linguistic gap between Mandarin and Bahasa Indonesia, particularly in the complexity and specificity of Mandarin linguistic rules. To bridge this gap, this study proposes the Material Description Table, a structured reference tool designed to optimize Mandarin language acquisition for Indonesian learners. Additionally, this research highlights the potential for future AI-driven language learning applications, where the Material Description Table could serve as a foundation for intelligent language-learning technologies.